2013 IEEE Symposium on Computational Intelligence in Control and Automation (CICA) 2013
DOI: 10.1109/cica.2013.6611656
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced monitoring using PCA-based GLR fault detection and multiscale filtering

Abstract: One of the most popular multivariate statistical methods used for data-based process monitoring is Principal Component Analysis (PCA). In the absence of a process model, PCA has been successfully used as a data-based FD technique for highly correlated process variables. Some of the PCA detection indices include the T 2 or Q statistics, which have their advantages and disadvantages. When a process model is available, however, the generalized likelihood ratio (GLR) test, which is a statistical hypothesis testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The PCA algorithm was widely used in various fields of research data analysis, especially suitable for analyzing two-dimensional data matrix [38]. Researchers found that PCA could well express the basic features of the original data with less data [39]. Therefore, P300 EEG signals still retain the integrity of original EEG signals after PCA dimensionality reduction.…”
Section: Discussionmentioning
confidence: 99%
“…The PCA algorithm was widely used in various fields of research data analysis, especially suitable for analyzing two-dimensional data matrix [38]. Researchers found that PCA could well express the basic features of the original data with less data [39]. Therefore, P300 EEG signals still retain the integrity of original EEG signals after PCA dimensionality reduction.…”
Section: Discussionmentioning
confidence: 99%
“…• One of the biggest advantages of multiscale representation is its capacity to distinguish measurement noise from useful data features (Harrou et al, 2013b;Madakyaru et al, 2013b) by applying low-and high-pass filters to the data during multiscale decomposition. This allows the separation of features at different resolutions or frequencies, which makes multiscale representation a better tool for filtering or denoising noisy data than traditional linear filters, like the mean filter and the exponentially weighted moving average (EWMA) filter (Sheriff et al, 2014).…”
Section: Advantages Of Multiscale Representation In Pls Modelingmentioning
confidence: 99%
“…One of the biggest advantages of multiscale representation is its capacity to distinguish measurement noise from useful data features [53,54], by applying low and high pass filters to the data during multiscale decomposition. This allows the separation of features at different resolutions or frequencies, which makes multiscale representation a better tool for filtering or denoising noisy data than traditional linear filters, like the mean filter and the exponentially weighted moving average (EWMA) filter [48].…”
Section: Multiscale Data Filtering Algorithmmentioning
confidence: 99%